A Systematic Literature Review: Computational Thinking dalam Pembelajaran Matematika - Evi Nur; Jarnawi Afgani Dahlan; Syifa Shafira; Sugeng Sungkono (Square : Journal of Mathematics and Mathematics Education, 2025)
This study analyzes the integration of Computational Thinking (CT) in formal mathematics education across school levels from 2020 to 2025 using the Systematic Literature Review method with the PRISMA protocol. Through strict selection on the Scopus database limited to final journal articles, written in English, full text access, and focused on core mathematics learning, 10 eligible articles were found. This limited number shows that empirical research with global reputation in this field is still rare. The critical analysis reveals that the impact patterns in the field are conditional and do not merely show a general positive impact. The success of CT integration is directly related to students' basic mathematics skills. Weak initial competence actually triggers thinking difficulties and conceptual misunderstandings due to different meanings between programming language rules and conventional algebra symbols. This study offers novelty by mapping a clear shift in CT integration, which is no longer just a separate basic visual programming tool, but has merged into specific mathematics topics and modern technology ecosystems such as Scratch, GeoGebra, and AI. The study concludes by emphasizing the need for adaptive learning materials, specific CT assessment tools, continuous teacher training, and wider empirical research in various educational contexts. Keywords: computational thinking; mathematics learning; systematic literature review.